Knowledge and practice of beginner and veteran (men and women) nurses in the hospital scenario - Santo, Fátima Helena do Espírito (Online Brazilian Journal of Nursing, 2004)
The survey compares the care of nursing in the hospital scenario between the perspectives of beginners and veteran nurses, being its objectives: to identify the distinctive characteristics of this care for these professionals and to analyze the implications of these characteristics for the knowledge and practice of nurses who work in the hospital scenario. From the “Nightingalean’s” principles associated to the contemporary perspectives on the care in nursing, the study of the qualitative nature was subsidized by quantitative techniques for the treatment, classification and categorization of the individual information according to the method of content associations and as collective results it has emerged four dimensions of the caring, namely: professional, knowledge, affection and practice, which interrelate in the professional working of the study’s subjects. It is concluded that during the professional development of beginners and veteran nurses there are characteristics related to the care in nursing that are kept during the graduation and the professional practice. Other characteristics suffer a movement of transformation since the beginning of the professional work, configuring a process that is kept during the practice within the hospital scenario. Thus, the knowledge and the practice of these (men and women) nurses presented a dynamic of accommodation that although preserves the “Nightingalean’s” principles of the profession, involves other characteristics that are determined by the institutions and are incorporated during the professional practice.